Northwest History. Box 3. Farms and Farming. Potatoes. United States. (1936)
Certified Potato Crop Sets Record. CERTIFIED POTATO CROP SETS RECORD BOISE, Idaho.-Production of certified seed potatoes in 1935 is not only the largest on record but was more than 50 per cent greater than the average of the five years prior to 1934, according to Richard C. Ross, agricultural statistician, of the division of crop and livestock estimates. Production of certified seed potatoes in 1935 was not only the largest on record but was more than fifty per cent greater than the average of the five years prior to 1934. Reports submitted to the U. S. bureau of agricultural economics by the certifying agencies in the 25 states where seed potato certification work is conducted show a total production in 1935 of 12, 093,060 bushels compared with 10,459,865 bushels in 1934 and a 5-year (1929-33) average of 7,795,000 bushels. In nine states the production was substantially larger than in 1934. The increases were mostly in the North Central states, Minnesota, North Dakota and Nebraska accounting for more than the total increase over 1934 and for 30 per cent of the total production. In all of the Atlantic, South Central and North Pacific States the production was less than in 1934. Prices offered growers on December 1 as compared with those offered on the same date in 1930 varied greatly. In the North Atlantic' states they were generally considerably higher than a year ago up to double the price in some states. In the large-producing North Central states of Minnesota, North Dakota and Nebraska and in some of the Western states the price ranged from the same to 30 per cent lower than in 1934. In some of the states not a sufficient number of sales had been made by December 1, to establish a price.